Lower Gastrointestinal Bleeding (Nonvariceal): Concepts and Technique - Marri, Uday Kumar; Singh, Jagadeesh R.; Pal, Partha; Modak, Shreeyash (Digestive Disease Interventions, 2024)
Lower gastrointestinal bleeding (LGIB) is defined as bleeding from the GI tract anywhere distal to the ligament of Treitz. It has multiple causes, including colonic diverticula, hemorrhoids, inflammatory bowel disease, and neoplasms. LGIB presents a wide spectrum of clinical manifestations, ranging from acute presentations with massive bleeding to insidious presentations with chronic, low-grade, intermittent bleeding. Although LGIB is less common and generally less severe compared with upper GI bleeding (UGIB), approximately 10 to 15% of cases eventually require endovascular intervention. Because of the unique vascular anatomy and potential complications, it often necessitates more specialized endovascular skills compared with UGIB. Embolization of LGIB carries a higher risk of ischemic complications compared with UGIB, as the superior mesenteric artery and the inferior mesenteric artery have a less rich collateral supply compared with the celiac trunk. The management of LGIB depends on its etiology, location, and severity. A multidisciplinary team approach, including gastroenterologists, surgeons, and interventional radiologists, is vital for achieving the best possible outcomes for these patients. With advances in microcatheter technology and newer embolic agents, interventional radiologist plays an increasingly important role in LGIB. Interventional radiologists managing these patients should have good knowledge of mesenteric arterial anatomy, the properties of different embolic agents, and basic principles of superselective embolization. In this comprehensive review, we discuss how to approach a patient with LGIB and the role of the interventional radiologist in these patients. Furthermore, we delve into endovascular techniques and concepts for superselective embolization and various embolic agents used in LGIB.
Keywords: lower gastrointestinal bleeding; interventional radiology; mesenteric angiography; embolization; endovascular management